2016
DOI: 10.1002/2016jd025393
|View full text |Cite
|
Sign up to set email alerts
|

The impact of revised simplified Arakawa‐Schubert scheme on the simulation of mean and diurnal variability associated with active and break phases of Indian summer monsoon using CFSv2

Abstract: The impact of revised simplified Arakawa‐Schubert (RSAS) convective parameterization scheme in Climate Forecast System (CFS) version 2 (CFSv2) on the simulation of active and break phases of Indian summer monsoon (ISM) has been investigated. The results revealed that RSAS showed better fidelity in simulating monsoon features from diurnal to daily scales during active and break periods as compared to SAS simulation. Prominent improvement can be noted in simulating diurnal phase of precipitation in RSAS over cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 61 publications
(84 reference statements)
3
18
0
Order By: Relevance
“…In order to gain further insight into the precipitation and moisture processes over the core CI region (18 • −27 • N and 74 • −85 • E), we have analysed the vertical profile of RH as a function of the rain rate during JJAS of 2016-2017 (figure 10). This metric has been proved to be useful to look into the model moist dynamic processes (Thayer-Calder and Randall 2009;Ganai et al 2016;Abhik et al 2017). It is evident that for all lead times, the model is able to capture the vertical pattern of rainfall and RH pattern broadly.…”
Section: Evaluation Of Rainfall and Dynamical Parametersmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to gain further insight into the precipitation and moisture processes over the core CI region (18 • −27 • N and 74 • −85 • E), we have analysed the vertical profile of RH as a function of the rain rate during JJAS of 2016-2017 (figure 10). This metric has been proved to be useful to look into the model moist dynamic processes (Thayer-Calder and Randall 2009;Ganai et al 2016;Abhik et al 2017). It is evident that for all lead times, the model is able to capture the vertical pattern of rainfall and RH pattern broadly.…”
Section: Evaluation Of Rainfall and Dynamical Parametersmentioning
confidence: 99%
“…Another important aspect of the model is the diurnal rainfall variation, namely, the diurnal phase and the diurnal absolute amplitude (figure 11a and b). The definition of the diurnal phase is that the local solar time when the maximum precipitation occurs in a day (Ganai et al 2016). Diurnal absolute amplitude is defined as the difference between maximum rainfall and minimum rainfall in a day (Ganai et al 2016).…”
Section: Evaluation Of Rainfall and Dynamical Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, Grell and NSAS are non-scale-aware but have shown good performance in simulating summer precipitation over Asia (e.g. Ganai et al 2016;Yang et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Ganai et al . [] employed the revised SAS scheme for long simulations in CFS and showed that the performance of the model improves in simulating diurnal variability and mean climate during the boreal summer. However, the ratio between convective and large‐scale rainfall over global tropics did not show any improvement.…”
Section: Introductionmentioning
confidence: 99%